Integrasi Wisata Halal dan Industri Kerajinan Mutiara Dalam Perspektif Islam - Dewi, Novi Yanti Sandra; Hulaimi, Ahmad Ahmad; Abdillah, Muhammad Zaki (Jurnal Ilmiah Ekonomi Islam, 2024)
This study explores the integration of halal tourism and the pearl craft industry in Indonesia through an Islamic perspective, using a constructivist paradigm and a qualitative case study approach. The research is driven by the fundamental issue of the need to develop the halal tourism sector in a way that not only fulfills the spiritual needs of Muslim tourists but also supports local industries such as pearl crafting. The objective of this study is to analyze how Islamic principles can be holistically applied in the development of this sector, as well as to evaluate the social, cultural, and economic impacts of this integration on local communities. The research methodology employed is a qualitative approach with a case study in Lombok, involving in-depth interviews, observations, and document analysis. The findings indicate that the integration of halal tourism and the pearl craft industry has the potential not only to enhance the local economy but also to strengthen the cultural and religious identity of the local community.